Perfil epidemiológico e morbimortalidade precoce de pacientes vítimas de sepse atendidos no Hospital Regional Norte - Oliveira Filho, Aldenir Rocha de (2022)
INTRODUCTION: Sepsis is a clinical syndrome that presents abnormalities caused by a dysregulated inflammatory response to infection. OBJECTIVE: To analyze the epidemiological profile of patients treated at Hospital Regional Norte, Sobral, Ceará. Identify within the sepsis management protocol factors that influence the outcome of these patients. METHODS: A sample of 1360 medical records of patients affected by sepsis admitted to the North Regional Hospital from January/2019 to February/2020 was used. Data were processed and analyzed by Microsoft Excel (version 16.53), followed by statistical analysis using the R v language. 3.6.0 using the R Studio Integrated Development Environment v. 1.2.1335. We studied the patient profile, outcome and rate of protocol compliance and hospital sepsis. RESULTS: It was observed that the majority of those affected by sepsis were men, 51.69%, with a mean age of 51 years. Most cases were of community origin 67.13% with a pulmonary focus 53.67%. Of the patients evaluated, 45% remained up to 7 d (days) in hospital, 25% between 7-14 d and 30% were hospitalized for more than 14 d. Regarding the outcome, 45.64% progressed to discharge and 43.03% to death. The compliance rate ranged from 56.65% (Reassessment of volume and perfusion status) to 89.57% (Opening the sepsis protocol in a timely manner). CONCLUSION: The results presented partially corroborate existing data in the academic literature and suggest that the training of professionals from the multidisciplinary team to identify and initiate the sepsis protocol can improve the prognosis of the patient's outcome. Statistically, timely protocol opening was related to patient outcomes.